A Case of Lithium Encephalopathy with Therapeutic Lithium Levels: The Diagnostic Role of EEG. (16th December 2022) - Carmassi, Claudia; Nardi, Benedetta; Battaglini, Simone; Bonelli, Chiara; Violi, Miriam; Bonanni, Enrica; Dell'Osso, Liliana
Abstract : Introduction . Lithium is considered a first-line therapy for both the acute phase and the maintenance of bipolar disorder. Many studies highlighted its neuroprotective and neuroplastic capacity suggesting a potential usefulness in the treatment of neurodegenerative diseases. Despite the undeniable efficacy, lithium clearly presents several adverse effects including neurotoxicity, also known as lithium encephalopathy, regarding both neurological, psychiatric, and cognitive side effects. In this case, adverse reactions are not always related to its serum levels, possibly appearing within the therapeutic range. Case Presentation . We analyzed the case of a bipolar patient who has been uncontinuosly treated with lithium salts since the onset of the psychopathological picture. Over the years, the average values of lithemia always remained around 0.60-0.70 mEq/L, but in 2019, the patient begun to manifest distal tremors and in the mandibular district accompanied, in the following months, by psychomotor slowdown, generalized tremors, reduced alertness, spatiotemporal disorientation, and aphasia. While alterations referable to neurodegenerative diseases were excluded, EEG maintained rhythm alteration 1 year after the probable intoxication. Discussion . This case confirms the central role of EEG for lithium neurotoxicity, while its dosages are in therapeutic range, being plasma levels are not always indicative of liquoral and neuronal lithium's levels. We highlight the importance of an early diagnosis of lithium encephalopathy proposing EEG as an indispensable tool for assessing lithium neurotoxicity both in acute and chronic intoxication.